KAPABILITAS APARATUR PEMERINTAH KECAMATAN DALAM PENGAWASAN PERTAMBANGAN TANPA IZIN (PETI) DI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Alwin Doni; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Unlicensed mining (PETI) is a serious problem, so the supervision of Unlicensed Mining (PETI) in Cerenti Sub-district requires the integration of resources or involving many parties in Cerenti Sub-district, especially the sub-district government apparatus. Various methods have been undertaken in the supervision of Unlicensed Mining (PETI) by Cerenti District Integrated Team. The problems of this research are (1) What is the capability of the sub-district government apparatus in the supervision of Unlicensed Mining (PETI) in Cerenti Sub-district Kuantan Singingi District? The purpose of this research are (1) to know the capability of sub-district government apparatus in supervision of Unlicensed Mining (PETI) in Cerenti Sub-district Kuantan Singingi Regency. This research method is qualitative research method with phenomenology approach.The conclusion of this research mentioned that the implementation of supervision of Unlicensed Mining (PETI) in Cerenti District is not yet maximal, but the implementation of Unsecured Mining (PETI) supervision has been in accordance with the Decision Letter of Regent Number 13 Year 2013 regarding the establishment of Integrated Team. However, the lack of follow-up done by the kecamatan is due to the absence of special budget and other supporting training which can assist in the implementation of Unsecured Mining (PETI) supervision in Cerenti Sub-district.Keywords: Supervision, Unlicensed Mining